The Truth Will Set You Free? The Promises and Pitfalls of Truth‐Telling for Indigenous Emancipation - Maddison, Sarah; Hurst, Julia; Thomas, Archie (Cogitatio Press, 2023)
First Nations in Australia are beginning to grapple with processes of treaty‐making with state governments and territories. As these processes gain momentum, truth‐telling has become a central tenet of imagining Indigenous emancipation and the possibility of transforming relationships between Indigenous and settler peoples. Truth, it is suggested, will enable changed ways of knowing what and who “Australia” is. These dynamics assume that truth‐telling will benefit all people, but will truth be enough to compel change and provide an emancipated future for Indigenous people? This article reports on Australian truth‐telling processes in Victoria, and draws on two sets of extant literature to understand the lessons and outcomes of international experience that provide crucial insights for these processes—that on truth‐telling commissions broadly, and that focusing specifically on a comparable settler colonial state process, the Canadian Truth and Reconciliation Commission. The article presents a circumspect assessment of the possibilities for Indigenous emancipation that might emerge through truth‐telling from our perspective as a team of Indigenous and non‐Indigenous critical scholars. We first consider the normative approach that sees truth‐telling as a potentially flawed but worthwhile process imbued with possibility, able to contribute to rethinking and changing Indigenous–settler relations. We then consider the more critical views that see truth‐telling as rehabilitative of the settler colonial state and obscuring ongoing colonial injustices. Bringing this analysis into conversation with contemporary debate on truth‐telling in Australia, we advocate for the simultaneous adoption of both normative and critical perspectives to truth‐telling as a possible way forward for understanding the contradictions, opportunities, and tensions that truth‐telling implies.